Implementation of Load cell Sensors as Monitoring the Weight of Infusion Fluids in Inpatients Based on Internet of Things (IoT): Implementasi Sensor Load cell Sebagai Pemantau Berat Cairan Infus Pada Pasien Rawat Inap Berbasis Internet of Things (IoT) - Vila, Vila Puspita Devi; Taufiqurrohman, Muh.; Subur, Joko (Muhammadiyah University, Sidoarjo, 2025)
The use of electronics for medical purposes is currently very much needed, especially for monitoring infusion fluids. Infusion plays an important role in supporting the needs of inpatients as medicine, vitamins or replacing the patient's body fluids. One problem that often arises is the delay in replacing infusion fluid bags that have run out. If the infusion fluid runs out and the replacement is late, blood from the vein can enter the infusion tube, as well as air bubbles entering the vein. This condition can be fatal because blood flow is disrupted, and the oxygen the body needs cannot be distributed through the blood, so the body's organs will lack oxygen. Currently it is still controlled manually, so with research on an infusion monitoring system using a Load cell sensor which can be monitored remotely, it makes the nurse's time more efficient. In this research, the results of tests that have been carried out regarding load cell sensor readings have a 100% success rate in detecting the weight of infusion fluid from full condition until the fluid is considered finished and the data can be sent in real-time to Android by utilizing Internet of Things (IoT) technology.